RENCANA ANGGARAN BIAYA DAN METODE PELAKSANAAN PADA PROYEK PEMBANGUNAN JALAN AKSES PELABUHAN PERIKANAN LAMPULO STA 0+-000 SID 1+-013 KOTA BANDA ACEH - Muhammad Irfan (Portal: Jurnal Teknik Sipil, 2016)
Lampulo Fishing Port Road Access Project, Banda Aceh City with 1013 m of road length, 10 m road width, base course layer 15 cm thickness, subcase 20 cm layer, 6 cm surface Aspalt Concrete Binder Course (AC BC) and Talud work . This Final Project aims to determine the method of implementation and budget costs on the project. The calculation of the Budget Plan uses the EI Analysis (Estimated Index) to calculate the cost of Sub Base, Base Course, Prime Coat, Surface Aspalt Concrete Binder Course (AC-BC), and Talud work. In this calculation, the cost for Sub Base work is Rp.1.027.631.772,00, -. Work Base Course Rp.970.243.296, 00, -. Prime coat job Rp.121.358.725,00, -. Surface layer work Aspalt Concrete Binder Course (AC-BC) Rp.1.906.855.195,00, Talud Work Rp.2.639.141.122, 00, -. So the total cost of the budget is Rp.6.695.230.109, 00. As well as scheduling the implementation time using the curve S. The preparation of the Implementation method applied to the Project includes Sub Base, Base Course, Prime Coat and Surace Aspalt Cpncrete Binder Course (AC-BC) work in an effective and efficient manner based on the drawing of the plan.Keywords: Budget Costs, S Curve, and Methods of Accounting.